Provenance study of oyster shells by LA-ICP-MS. (August 2021) - Mouchi, Vincent; Godbillot, Camille; Dupont, Catherine; Vella, Marc-Antoine; Forest, Vianney; Ulianov, Alexey; Lartaud, Franck; de Rafélis, Marc; Emmanuel, Laurent; Verrecchia, Eric P.
Abstract: Provenance determination of archaeological remains is a valuable tool for reconstruction of past exchange networks. Among these materials, oyster shells are ubiquitous in sites from all prehistorical and historical periods. Thus, they seem to be promising candidates for provenance identification as they include chemical elements from the environment in their shells, which implies that an elemental fingerprint of the region of origin can be recorded in the shell composition. In this study, we present elemental measurements from 15 groups of modern and archaeological shells from 13 continental localities in mainland France and the island of Corsica (western Mediterranean Sea). Two of these localities had two oyster species ( Crassostrea gigas and Ostrea edulis ). Results indicate that (i) a species-specific elemental fingerprint exists and (ii) the Atlantic Ocean and Mediterranean Sea provenances can be identified for O. edulis shells. Moreover, if the shell originated from a locality only partially connected to the ocean ( e.g. an estuary or lagoon), a fingerprint specific to the watershed can also be observed, even between groups originating from the same bay. Using these measurements as reference fingerprints, we characterize the Mediterranean origin of two groups of shells unearthed at Lyons (central France, 200 km away from the nearest shoreline), dated from the 1st c. CE. Highlights: Elemental fingerprinting from 15 groups of oyster shells is measured by LA-ICP-MS Local fingerprints are different between two oyster species ( C. gigas and O. edulis ) Discrimination of origin of large water bodies (sea and ocean) is possible Regional provenance can be identified if river inputs are sufficiently important Two groups of Antiquity shells from Lyons were identified as originating from the Mediterranean Sea